Dual Element (C/Cl) Isotope Analysis Indicates Distinct Mechanisms of Reductive Dehalogenation of Chlorinated Ethenes and Dichloroethane in Dehalococcoides mccartyi Strain BTF08 With Defined Reductive Dehalogenase Inventories - Franke, Steffi; Seidel, Katja; Adrian, Lorenz; Nijenhuis, Ivonne (Frontiers in Microbiology, 2020)
Dehalococcoides mccartyi strain BTF08 has the unique property to couple complete dechlorination of tetrachloroethene and 1,2-dichloroethane to ethene with growth by using the halogenated compounds as terminal electron acceptor. The genome of strain BTF08 encodes 20 genes for reductive dehalogenase homologous proteins (RdhA) including those described for dehalogenation of tetrachloroethene (PceA, PteA), trichloroethene (TceA) and vinyl chloride (VcrA). Thus far it is unknown under which conditions the different RdhAs are expressed, what their substrate specificity is and if different reaction mechanisms are employed. Here we found by proteomic analysis from differentially activated batches that PteA and VcrA were expressed during dechlorination of tetrachloroethene to ethene, while TceA was expressed during 1,2-dichloroethane dehalogenation. Carbon and chlorine compound-specific stable isotope analysis suggested distinct reaction mechanisms for the dechlorination of (i) cis-dichloroethene and vinyl chloride and (ii) tetrachloroethene. This differentiation was observed independent of the expressed RdhA proteins. Differently, two stable isotope fractionation patterns were observed for 1,2-dichloroethane transformation, for cells with distinct RdhA inventories. Conclusively, we could link specific RdhA expression with functions and provide an insight into the apparently substrate-specific reaction mechanisms in the pathway of reductive dehalogenation in D. mccartyi strain BTF08.